Interpreting art in museums and galleries - Whitehead, Christopher, 1972- (Abingdon, Oxon [England] ; New York, NY : Routledge, 2012)
In this carefully focused book, Christopher Whitehead presents both a study of and guide to curatorial practices of art interpretation, including the manipulation of the physical display environment and the production of supporting materials, from text panels to audioguides and interactives.
pt. 1. Introductory mappings. What is art interpretation? Why interpret art? ; The cultural cartography of the museum ; Matters of interpretation : materiality, authority, chronology -- pt. 2. Interpretive practice today. Interpretive frames : historical figurative art ; Interpretive frames : modern, contemporary and non-figurative art ; Case studies : institutional approaches to historical art ; Case studies : institutional approaches to contemporary art ; Interpretive futures.
Includes bibliographical references (p. [183]-188) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Art museums -- Educational aspects; Art -- Study and teaching; Art and society; Art appreciation; Electronic books